Exploring the experiential aspect of home-stay in Kampung Lonek using diary method - Musa, G.; Thirumoorthi, T. (2008)
Home-stay is one of the Malaysian government efforts to diversify its cultural tourism product. Tourists are adopted by their foster families and experience the traditional life in Malay villages. This study explores the experiential aspects of home-stay holidays in Kampung Lonek using diary method. Nineteen diaries were returned and were analyzed using NVIVO. The paper proposed a home-stay experiential model which explains the phases of travel experience including the on-site experience. Among the on-site experience dimensions are 'Environmental Experience', 'Activity, Culture and Knowledge Experience' and 'Human Interaction Experience'. The uniqueness of home-stay experience is discussed along with some management implications.